Perceived Social Support and Mental Health Help-Seeking Attitude of Parents of Learners with Intellectual Developmental Disorder: Inputs for Psychosocial Support Program - Jose Rainier Gallego Penales (Universitas Katolik Soegijapranata, 2026)
Lack of psychosocial support programs for parents of children with disabilities leaves them highly vulnerable to stress, financial hardship, and social isolation. Therefore, this study aimed to analyze the level of the participants' perceived social support from family, friends, and significant others and their mental health help-seeking attitude in terms of psychological openness, help seeking propensity, and stigma indifference. The study employed a correlational design to gather the research data, and utilized the Multidimensional Scale of Perceived Social Support (MSPSS) and the Attitudes toward Seeking Mental Services (IASMHS). The participants in this study were 207 adults (aged 18-65) who have children with intellectual developmental disorder enrolled in a special education curriculum in a public school in the city schools division of Bacoor, Cavite; they were selected using a purposive method because of their shared criteria that fit the study. The findings determined that there is significant positive monotonic relationship between perceived social support and mental health help-seeking, with Spearman rank correlation coefficient of 0.156 and p-value of 0.024. This suggests that as perceived availability of social support increase, confidence to seek professional mental health assistance also increase.